Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Konsumen Produk Pakaian Dalam Pria PT. Colorindo Internusa di Carrefour Tangcity Mall: BRAND IMAGE AND PRICE ON PURCHASE DECISION - Tri Angreni; Denis Lupie (eCo-Buss, 2021)
Nowadays, with the help of the internet, all information can be obtained quickly and easily including information about all products, this makes consumers smarter and more critical in choosing a product. Sales of men's underwear with the Mario Marcello brand are still not satisfactory from the target set by the company, which is likely due to the increasing competition among similar product providers, which requires the company to be able to compete for new customers and be more vigilant in retaining its customers. This study aims to determine how much the effect of the brand image and price have on purchasing decisions for men's underwear, Mario Marcello brand at Carrefour Tangcity Mall. This type of research uses quantitative descriptive methods. The population that used is the male consumer of Mario Marcello’s product at Carrefour Tangcity Mall and the sample taken is 100 respondents. From the results of data analysis with the correlation coefficient test, it shows that Brand Image and Price have a positive and strong relationship with Purchasing Decisions. From the results of data analysis with the T hypothesis test shows that brand image and price have a significant effect on purchasing decisions. Hypothesis F test shows that there is a linear effect between the Brand Image and Price variables on Purchasing Decisions, so the regression model is appropriate and feasible.